Perbedaan Kadar Prokalsitonin Pada Anak Sepsis Dan Sepsis Berat Berusia 3-36 Bulan - Maria Atik Wijayanti; Irene Ratridewi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Sepsis is one of the causes of high morbidity, mortality and length of hospitalization, especially infants. The incidence of severe sepsis in children is estimated at 40,000 cases per year, with 10-15% of progressing to septic shock. The clinical diagnosis of sepsis is difficult because of the nonspecific signs and symptoms, such as fever.Methods: Design research is pre experiment with case control descriptive analytic for procalcitonin in severe sepsis and sepsis. There are 40 children aged 3-36 months with sepsis and severe sepsis. Data were analyzed statistically using normality test is then followed by different test independent test samples.Results: The results showed a significant difference between the levels of procalcitonin in sepsis patients as compared to the levels of procalcitonin in patients with severe sepsis.Conclusion: 1. The maximum procalcitonin at patients diagnosed with sepsis 290 ng / ml2. The maximum procalcitonin at patients diagnosed with severe sepsis 443 ng / ml3. there was significant difference between the levels of procalcitonin in sepsis patients as compared to the levels of procalcitonin in patients with severe sepsis with p-value = 0.000 (p<0.05)